PENENTUAN PORTOFOLIO OPTIMAL DENGAN MENGGUNAKAN SINGLE INDEX MODEL SEBAGAI ANALISIS SAHAM-SAHAM LQ45 (STUDI KASUS PADA BURSA EFEK JAKARTA) - Herdiyana herdiyana (Universitas Pakuan, 2018)
AbstractIn allocating fund or investment, an investor either asindividual or institution always confronts return and risk. Arational investors will focus their attention to (1) highestreturn with certain risk or (2) certain risk with low risk.Both conditions represent the optimal investment. One wayto reduce risk is by constructing portfolio, because by doingso, the risk can be diversified or spread among securitiesselected in the portfolio. The principle of ?dont put your alleggs into one basket? is the basic idea of investors inpracticing their investment. One of the model which can beused to determine or analyze securities in order to obtainthe optimal portfolio is single index model.This research is aimed to learn, analyze and conclude:(1) determination of stocks in LQ45 which are selected toconstruct the optimal portfolio optimal by using single indexmodel; (2) determination of fund allocation, calculatereturn and risk of optimal portfolio that will be earned byinvestor from selected stocks in optimal portfolio by usingsingle index mode.The research concludes: (1) By using single indexmodel procedure which are ERB ratio and cutoff rate, sevenstocks are selected to construct the optimal portfolio whichinclude AALI, INCO, CMNP, UNSP, LSIP, SMRA, and BNGA;(2) The proportion of fund allocation for each stock are asfollow: 28,27% in AALI, 16,43% in INCO, 12,04% in CMNP,13,96% in UNSP, 10,80% in LSIP, 14,35% in SMRA and4,16% in BNGA. Portfolio return earned by investors if theyinvested their fund in those seven stocks with the proportionas mentioned earlier is 41,29%. The possible risk that theinvestors can receive is measured by standard deviation ofportfolio which is 1, 52.Key words : Single Index Model : Excess Return to Beta,Cutoff Rate, Portfolio Return and Risk..